Analysis of Maternal Anxiety Levels in Breastfeeding Practices at Primary Healthcare Facilities during the Pandemic Transition - Sartika, Yuni Ayu; Fauziah, Nurul (CV. Social Politic Genius (SIGn), 2024)
The COVID-19 pandemic has created persistent psychological challenges for breastfeeding mothers, where concerns regarding infection and situational uncertainty potentially inhibit the physiological mechanism of lactation through oxytocin suppression. Although the acute phase of the pandemic has passed, mapping the mental condition of breastfeeding mothers at the primary healthcare level (Independent Midwifery Practices) remains rarely explored compared to studies in referral hospitals. This study aimed to provide an overview of maternal anxiety levels regarding breastfeeding during the 2022 pandemic transition period at Independent Midwifery Practice (IMP) W. It employed a quantitative descriptive approach with a cross-sectional design. The research sample consisted of 73 breastfeeding mothers, selected purposively from a population of 194 respondents. The research instrument used an anxiety questionnaire, which was analyzed univariately to generate frequency distributions and characteristic proportions. The results showed that the majority of respondents (60.27%) experienced mild anxiety, while 39.73% experienced no anxiety, with no cases of moderate or severe anxiety found. Specifically, this mild anxiety profile was substantially concentrated in vulnerable groups, namely mothers with a basic educational background (70.45%) and unemployed mothers/homemakers (70.45%). This study concludes that the pandemic residue manifests as mild yet chronic hypervigilance, particularly among groups with limited health literacy. These findings recommend the urgency of integrating routine mental health screening and personalized lactation education into primary midwifery care to prevent exclusive breastfeeding failure due to latent anxiety.